DETERMINATION OF TIME THROUGH THE OBSERVATION OF TWO STARS AT DIFFERENT ALTITUDES WITHOUT A KNOWLEDGE OF THE LATITUDE - TOSCANO, R (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
The method for the determination of time may be used when the latitude of the place of observation is not know with the accuracy desired. Nevertheless this method has the advantage of observed only two stars at any altitude, affording thus the determinati
BOL OBS TONAN TACUB
Keywords: DETERMINATION, TIME THROUGH, OBSERVATION, TWO STARS, DIFFERENT ALTITUDES, WITHOUT, KNOWLEDGE, LATITUDE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS